Diffuse myocardial fibrosis and the prognosis of heart failure with reduced ejection fraction in Chinese patients: a cohort study - Li, Fuhai; Xu, Mengying; Fan, Yuyuan; Wang, Yanyan; Song, Yu; Cui, Xiaotong; Fu, Mingqiang; Qi, Baozheng; Han, Xueting; Zhou, Jingmin; Ge, Junbo (The International Journal of Cardiovascular Imaging, 2020)
Evidence regarding the relationship between diffuse myocardial fibrosis and the prognosis of heart failure with reduced ejection fraction (HFrEF) was limited. Therefore, this study set out to investigate whether diffuse myocardial fibrosis was independently related to the prognosis of failure with reduced ejection fraction in Chinese patients after adjusting for other covariates. The present study was a cohort study. A total of 45 consecutive HFrEF patients were involved in Zhongshan Hospital of Fudan University in China from 1/9/2015 to 31/12/2016. The target-independent variable was extracellular volume (ECV) quantified by cardiac magnetic resonance T1 mapping using the modified Look-Locker inversion recovery (MOLLI) sequence at baseline. To assess the prognostic impact of MOLLI–ECV, its association with hospitalization for heart failure/cardiac death was tested by multivariable Cox regression analysis. Covariates involved in this study included age, gender, body mass index, heart rate, systolic blood pressure diastolic blood pressure, smoking, hypertension, diabetes mellitus, etiology, NYHA functional class, blood urea nitrogen, creatinine, serum uric acid, total bilirubin, and growth stimulation-expressed gene 2. Ten age- and sex-matched healthy participants with no history of cardiovascular disease served as a control group. Mean MOLLI–ECV was significantly higher in HFrEF patients versus healthy controls (29.55 ± 1.46% vs. 23.17 ± 1.93%, P < 0.001). Patients were followed for 9 months, during which the primary outcome (cardiac death or first heart failure hospitalization) occurred in 15 patients. By Kaplan–Meier analysis, patients with high MOLLI–ECV ≥ 30.10% had shorter event-free survival than the middle (MOLLI–ECV between 30.10 and 28.60) and low (MOLLI–ECV < 28.60) MOLLI–ECV patients (log-rank, P = 0.0035). Result of fully-adjusted multivariable Cox regression analysis showed MOLLI–ECV was positively associated with the composite outcome of HFrEF patients after adjusting confounders hazard ratio (HR) 2.57, 95% CI (1.09, 6.04). By subgroup analysis, a stronger association was seen in patients who with NYHA functional class III–IV, hematocrit < 39.8%, left atrial diameter ≥ 53.5 mm, or without the medical history of MRA or diuretics other than MRA. The P for interaction was < 0.05. In HFrEF patients, the relationship between MOLLI–ECV determined by CMR and the composite outcome is linear. High MOLLI–ECV was associated with a higher rate of cardiac mortality and first HF hospitalization in the short term follow up.